Digital Marketing Strategies in Building Brand Advocacy to Improve Purchase Intention : (Study Case at PT. Nada Promotama) - Devita Chandra Aryn Ayuningtyas; Novika Candra Astuti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study investigates how digital marketing strategies affect online brand advocacy, brand loyalty, and purchase intention in the context of a music and event company in Indonesia, PT. Nada Promotama. Using a quantitative explanatory approach, data were collected from 281 respondents through an online survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that digital marketing significantly influences both online brand advocacy and brand loyalty. Moreover, brand loyalty positively and significantly affects purchase intention, while online brand advocacy does not have a direct significant effect. Interestingly, the analysis revealed a reciprocal relationship between brand advocacy and brand loyalty, suggesting a mutually reinforcing dynamic between the two constructs. These findings contribute to the understanding of digital consumer behavior in the entertainment sector and offer practical insights for marketers seeking to leverage emotional loyalty and advocacy in digital strategies.